Divorce Dynamics: Understanding the Causes and Consequences of a Growing world - Ali Bukhtiar; Usman Ghani Usmani; Muhammad Faiq Butt; Mohsan Iqbal (Indus Journal of Social Sciences, 2025)
Globally, divorce rates are rising, which represents a dramatic change in the dynamics of contemporary family and relationship dynamics. Economic independence, shifting expectations in partnerships, and shifting social standards are some of the elements driving this trend. Divorce presents significant difficulties for all parties, even though it might give people the strength to leave violent or toxic relationships. Children of divorced parents may face scholastic disruptions, social challenges, and developmental setbacks. Divorced parents also frequently suffer significant emotional, psychological, and financial tolls. This problem affects social structures on a larger scale, placing a burden on mental health services, social support networks, and legal institutions. This review investigates the reasons behind the rising divorce rates, dives into their complex effects, and looks at their wider societal ramifications. In order to lessen negative effects, it also emphasizes the necessity of preventative actions including relationship education, easily accessible counseling, and community-based support. In order to effectively handle this expanding global issue, the study ends with a plea for families and societies to develop resilience and flexibility.